STRESS-STRAIN-STRENGTH CHARACTERISTICS OF SOFT HONG KONG MARINE DEPOSITS WITHOUT OR WITH CEMENT TREATMENT - Jian-Hua Yin (Lowland Technology International, 2001)
This paper presents the results of triaxial tests on soft Hong Kong marine deposits (HKMD) without or with cement treatment. Special attentions are paid to the features of stress-strain relationships and the effective stress paths. Useful correlation (a) between index properties and strength parameters and (b) cement ratio and strength parameters and Young's modulus are presented. The data presented are of practical significance for design and construction of civil works on HKMD in Hong Kong.